The Management and Accounting Treatment of Confiscated Assets and Replacement Receivables at the Soppeng District Prosecutor’s Office - Zulfiana Zulfiana; Andi Muhammad Nurul Afdhal; Nur Achriaty Achmar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
Given the complexity of confiscated goods, they need to be assessed, recorded, and reported in accordance with government accounting standards. Meanwhile, compensation receivables must be recognized, measured, and monitored carefully to ensure the recovery of state losses. This study aims to examine how confiscated goods and compensation receivables are managed and treated in the accounting system of the Soppeng District Attorney's Office. This study refers to Government Accounting Standards (SAP), specifically PSAP Number 01 on Financial Statement Presentation and PSAP Number 05 on Inventory Accounting, as well as regulations related to the management of state property. The method used is a descriptive qualitative approach, with data collection techniques through interviews, observation, documentation, and literature study. The research findings indicate that the management of confiscated goods faces challenges such as discrepancies between the seizure records and the physical condition of the goods, which complicate the auction process. Additionally, damage to evidence items reduces their economic value. On the other hand, the management of compensation claims is hindered by delays in payments due to transactions outside bank operating hours and the risk of temporary storage in safes requiring strict supervision. From an accounting perspective, it is known that the recognition, measurement, presentation, and disclosure of confiscated goods and compensation receivables are in accordance with the principles and provisions outlined in the Government Accounting Standards (SAP), namely PSAP No. 01 and PSAP No. 05